The revealing processes of interpretation: Translating human rights principles into Pintupi-Luritja - Holcombe, Sarah (The Australian journal of anthropology, 2015)
The global language of English has emerged over the centuries as the language of human rights. This language embodies many Anglo key cultural concepts that we take for granted, related to some of our most fundamental epistemologies – such concepts as freedom, dignity, respect, reason and conscience, equality, individuality and the concept of ‘rights’ itself. By making explicit the cultural workings of these English concepts, and by considering English itself as a cultural universe, we can also examine Anangu core cultural concepts from a new perspective. A first step toward this juxtaposition of Anangu and English key cultural concepts is through the process of translating the Universal Declaration of Human Rights (UDHR) into Pintupi-Luritja. As Edward Sapir said in 1949, ‘vocabulary is a very sensitive index of the culture of a people’. This article will principally examine the first Article of the UDHR to elaborate Anangu cultural forms of morality and conceptions of personhood. That there is no ready parallel of these concepts in this local vernacular, a Western Desert language, both reveals ‘traditional’ socio-moral priorities and elides contemporary dialogical processes, as conversations begin to explicate, if not to translate.